Analysis of the ability of prospective biology teachers to develop teaching modules on the kampus mengajar program - Eko Sri Wahyuni; Mas Akhbar Faturrahman (University of Muhammadiyah Malang, 2024)
Kampus Mengajar is a program intended for university students in Indonesia to establish partnerships with schools and prepare themselves as future professional educators. Student participation in the Kampus Mengajar program requires mastery of pedagogical competencies, one of which is the development of teaching modules as a learning design that will be implemented. The purpose of this study was to describe the ability of Biology Education students of FKIP UNTAN to develop teaching modules, specifically, students who participated in the Kampus Mengajar Batch 6 (KM6). This research is descriptive qualitative research conducted by observing the completeness of the components of the 14 teaching modules developed. Based on the analysis conducted, it is known that the average percentage of general information is 98.81% with a very good category, the main components are 97.62% with a very good category, and the appendices are 78.57% with a good category. Overall, the average of all components is 92.44%, so it can be concluded that the ability of Biology Education students at FKIP UNTAN to develop teaching modules can be categorized as very good. The results obtained show that there are still flaws in the 14 teaching modules analyzed. Students need to develop their pedagogical professionalism so that their knowledge and skills in developing teaching modules increase.